2012
DOI: 10.4321/s1130-01082012000100002
|View full text |Cite
|
Sign up to set email alerts
|

Chromoendoscopy with red phenol in the diagnosis of Helicobacter pylori infection

Abstract: An analytic study to validate a diagnostic test was carried out at the Institute of Gastroenterology in Havana, Cuba in adult patients of both sexes in whom chromoendoscopy was carried out with red phenol at 0.1% over the gastric mucosa for the detection of Helicobacter pylori infection between November 2008 and December 2010. The staining with red phenol at 0.1% is included in the invasive tests for the diagnosis of Helicobacter pylori infection and of the reactive techniques. The sensibility of red phenol dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Such controversy might be due to the difference in sampling technique; as our study the sampling was endoscopic, while they obtained the biopsies after the operation with free access to every part of the stomach. Also Hernández-Garcés et al [ 14 ] study in Cuba on 195 patients showed a phenol red chromo-endoscopy sensitivity of 72.6% and specificity of 75.5% with Kappa coefficient of 0.4, with a positive predictive value of 89.8% and negative predictive value of 48.1% with diagnostic accuracy of 73.3%.…”
Section: Discussionmentioning
confidence: 98%
“…Such controversy might be due to the difference in sampling technique; as our study the sampling was endoscopic, while they obtained the biopsies after the operation with free access to every part of the stomach. Also Hernández-Garcés et al [ 14 ] study in Cuba on 195 patients showed a phenol red chromo-endoscopy sensitivity of 72.6% and specificity of 75.5% with Kappa coefficient of 0.4, with a positive predictive value of 89.8% and negative predictive value of 48.1% with diagnostic accuracy of 73.3%.…”
Section: Discussionmentioning
confidence: 98%
“…Conflicts were resolved by discussion until consensus was reached. The reviewers were not blind to the journal author names, author affiliations, and year of publication . Two‐by‐two tables were constructed in this study from each gene in all studies for the true‐positive (TP), false‐negative (FN), true‐negative (TN), and false‐positive (FP) values.…”
Section: Methodsmentioning
confidence: 99%
“…Altogether, histologic identification is a conventional test in the diagnoses of H. pylori infection with a mean sensitivity and specificity of 94% and 99%, respectively . This test is only performed following an endoscopy, and controversially, in a few studies, a lower sensitivity and specificity (73% and 76%, respectively) have been reported . Other tests including UBT, CLO (campylobacter‐like organism test), and PCR are also among the most reliable diagnostic techniques for the detection of H. pylori infection…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue of the Spanish Journal of Gastroenterology, Hernández-Garcés et al (15), from Cuba, report on a study for the validation of a diagnostic test: phenol red chromoendoscopy for the detection of H. pylori infection versus histology as gold standard. Phenol red staining sensitivity was 72.6% and specificity was 75.5%.…”
mentioning
confidence: 99%